Grade of dysplasia and malignant transformation in adults with premalignant laryngeal lesions. (13th August 2015) - van Hulst, Annelienke M.; Kroon, Wouter; van der Linden, Evi S.; Nagtzaam, Lily; Ottenhof, Sarah R.; Wegner, Inge; Gunning, Amy C.; Grolman, Wilko; Braunius, Weibel
Abstract: Background: The purpose of this systematic review was to determine the significance of the grade of dysplasia in the development of invasive carcinoma. Methods: A systematic search was performed to identify all relevant evidence. Titles and abstracts were screened using predefined criteria. Remaining articles were critically appraised. Absolute risks and 95% confidence intervals (CIs) were calculated. Results: Seven articles were included. Four studies demonstrated an increased risk for the development of laryngeal carcinoma from mild, moderate, and severe dysplasia. Three studies showed an increased risk between the categories of mild and moderate dysplasia. Conclusion: The risk of malignant transformation seems to increase with the grade of dysplasia, although percentages between studies are highly dissimilar. The wide variety and overlapping 95% CIs make it difficult to formulate a strong recommendation. However, moderate dysplasia is more prone for malignant transformation than previously thought, which might influence follow‐up and treatment decisions in the future. © 2015 Wiley Periodicals, Head Neck 38 : E2284–E2290, 2016